Phospholipases: at the crossroads of the immune system and the pathogenesis of HIV‐1 infection. Issue 1 (1st November 2016) - Cecchetti, Serena; Spadaro, Francesca; Gessani, Sandra; Podo, Franca; Fantuzzi, Laura
Abstract : Multiple host factors and their interactions with viral proteins contribute to the complexity of HIV‐1 pathogenesis and disease progression. The virus exploits the cell‐signaling networks to prepare the ground for viral replication, to affect functions of either infected or uninfected bystander cells, and to evade the immune response. These events are hallmarks of HIV‐1 pathogenesis that lead toward AIDS. Phospholipases are essential mediators of intracellular and intercellular signaling. They function as phospholipid‐hydrolyzing enzymes, generating many bioactive lipid mediators or second messengers, which control multiple cellular functions, thus regulating a variety of physiologic and pathophysiologic processes. These enzymes also represent important components of the cell‐signaling networks exploited by HIV‐1 and its proteins to favor viral replication and persistence, as well as immune response dysfunction. Although some individual phospholipases were studied in the context of HIV‐1 infection, the mechanisms whereby they regulate diverse infection‐associated processes, as well as the interaction among different phospholipases have yet to be fully elucidated. In this review, we discuss the principal aspects of the complex interaction between phospholipases, HIV‐1, and the immune system. A thorough understanding of the signaling networks that involve phospholipases in both HIV‐1–infected cells and individuals is essential to determine whether therapeutic targeting of these enzymes may represent a novel approach to control viral replication, as well as the associated inflammation and comorbidities. Abstract : Review of phospholipases as key players in HIV‐1 replication, and in associated dysfunctions of the immune system.